PEMAHAMAN MASYARAKAT TERHADAP TINGKAT KERENTANAN BENCANA TANAH LONGSOR DI DESA TOOBAUN KECAMATAN AMARASI BARAT KABUPATEN KUPANG - Mika Sampe Rompon; Julianus Dising; Basry Yadi Tang (Politeknik Pertanian Negeri Kupang, 2019)
The purpose of this research was to determine the society's understanding of disaster mitigation or preventing the likelihood of landslides, and efforts have been made public as well as solutions regarding prevention or reduction of the occurrence of landslides. This research was conducted in the Toobaun village of West Amarasi, Kupang district. The sampling technique was proportional random sampling. Sampling from entire population was taken as 100 respondents using descriptive analysis. The results showed that: 1) The level of public understanding about vulnerable to landslides and how to cope with and mitigate that are in the low category, where people suffered a lot of losses and damages caused by landslides, 2) Efforts have been made public categorized as high, and solutions in case of landslide still categorized low, people's knowledge and understanding of disaster mitigation less than the maximum so that the public is less aware of the potential damage caused by landslides. Keywords: The public's understanding, mitigation, landslides, Toobaun